Prevalence of dental injuries and awareness regarding mouthguards among basketball players and coaches - Tiryaki, M.; Saygi, G.; Yildiz, S. O.; Yildirim, Z.; Erdemir, U.; Yucel, T. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Dental injuries are frequently occurred by an impact to facial area among basketball players. In fact, mouthguards are able to absorb the power of impacts and protect teeth from excessive forces, it is crucial for players even at training to wear mouthguards. To determine the prevalence of dental injuries and investigate the awareness about the use of mouthguards among basketball players and coaches. METHODS: A 14-item questionnaire was designed and tested among licensed basketball players and coaches, all of whom were continuously exposed to the risk of dental injuries. The questions focused on the prevalence of dental injuries and attitudes and knowledge regarding the use of mouthguards among the players and coaches. Data were calculated using descriptive statistics and x2 tests. RESULTS: A total of 53 coaches (18-69 years) and 351 players (12-38 years) participated. Of these, 124 players (35% of the total sample) had experienced oral injuries, including soft tissue lacerations (80.6%), fractures (17.7%) and avulsions (1.6%). Although the players had sustained dental injuries, 95% of them found mouthguards to be protective, and only 6.3% (N.=22) actually used a mouthguard. The rate of mouthguard use among players who had experienced an oral injury was significantly higher than that among players without any history of injury (P<0.05). Although 98% of the coaches believed that mouthguards could prevent dental injuries, only 47% of them suggested their use to their players. The most common reasons for not using a mouthguard were discomfort (37.7%) and difficulty in breathing (7.3%) or talking (6.4%). CONCLUSIONS: This study showed that the use of mouthguards among basketball players is very rare, with inadequate knowledge among the coaches. Consequently, more information is required through sports associations and dentists.